Lutein-based dye vitrectomy for idiopathic epiretinal membrane: a pilot study - Rossi, Settimio; Gesualdo, Carlo; Della Corte, Michele; Del Giudice, Antonio; Rosolia, Andrea; Trotta, Maria Consiglia; Simonelli, Francesca (Frontiers in Medicine, 2025)
IntroductionThe use of vital dyes is essential for enhancing visualization of the vitreous and vitreoretinal interface during surgery. In this study, we evaluated the efficacy of a new lutein-based vital dye (LB-VD) for selective staining of the vitreous body and posterior hyaloid in patients undergoing 25 G vitrectomy for idiopathic epiretinal membrane (ERM).MethodsA total of 18 patients who underwent ERM surgery assisted by LB-VD were retrospectively analyzed. The surgeon completed a postoperative satisfaction questionnaire to evaluate the vitreous staining. Data on best-corrected visual acuity (BCVA), central retinal thickness (CRT), intraocular pressure (IOP), and fixation stability were collected at baseline and at 4 and 6 months post-surgery.ResultsLB-VD effectively stained the vitreous body and posterior hyaloid, facilitating key surgical maneuvers. Significant improvements were observed in BCVA and CRT at both 4 and 6 months post-surgery. Specifically, BCVA improved from 0.60 ± 0.29 LogMAR at baseline to 0.33 ± 0.26 LogMAR at 4 months (p = 0.004) and to 0.32 ± 0.25 LogMAR at 6 months (p = 0.003). CRT decreased significantly from 429 (375–499) μm at baseline to 335 (254–375) μm at 4 months (p = 0.03) and to 323 (240–356) μm at 6 months (p = 0.01). Fixation stability improved in approximately 95% of patients by 6 months. No significant changes in IOP were noted.DiscussionLB-VD provided clear visualization of the vitreous body and posterior hyaloid, thereby facilitating key vitreoretinal surgical tasks. These findings suggest that LB-VD is an effective and safe alternative to traditional dyes currently used in vitreoretinal surgery.